Communication for Farmer Empowerment in Social Capital Perspective (Study on Kalianget Salt Farmer Group in Sumenep Regency) - Roos Yuliastina; Irma Irawati Puspaningrum; Deny Fery Suharyanto; Moh. Kurdi (Institute of Educational, Research, and Community Service)
Community empowerment is an alternative development paradigm aimed at enhancing capacity and independence. However, this process cannot be fully achieved without participatory communication, since communicative actions within the community directly influence participation levels, allowing development to adapt to local characteristics. Therefore, this study integrates the empowerment communication paradigm with the perspective of social capital, which emphasizes togetherness and cooperation in addressing collective challenges. The research focuses on coastal communities in Kalianget Subdistrict to explore the role of social capital in the communication practices of salt farmer groups and to design an empowerment model grounded in social capital. This study employed a qualitative method with a case study approach. Data were collected through in-depth interviews with community leaders, salt farmer group leaders, and members, complemented by participatory observation and documentation studies. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing/verification, while data validity was strengthened through source and method triangulation. The findings reveal that three dimensions of social capital—social networks, trust, and values and norms—serve as the main pillars in the communication practices of salt farmer groups. Social networks were established through interactions based on mutual benefits, trust was reinforced through solidarity and reciprocity, and values and norms functioned as collective guidelines for both social and economic behavior. These findings affirm that communication rooted in social capital plays a significant role in strengthening community empowerment processes. Theoretically, this study enriches the discourse on empowerment communication, while practically it provides references for policymakers and communities in designing more adaptive empowerment strategies.